2015
DOI: 10.1109/tpel.2015.2506400
|View full text |Cite
|
Sign up to set email alerts
|

Single-Phase T-Type Inverter Performance Benchmark Using Si IGBTs, SiC MOSFETs and GaN HEMTs

Abstract: Abstract-In this paper, benchmark of Si IGBT, SiC MOSFET, 5 and Gallium nitride (GaN) HEMT power switches at 600-V class 6 is conducted in single-phase T-type inverter. Gate driver require-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(101 citation statements)
references
References 38 publications
0
101
0
Order By: Relevance
“…Practical implementation issues of the AT-NPC inverters using advanced WBG power semiconductor devices have got attentions in recent years [22] [23]. There still left many design and implementation issues for the integrated design and control of the AT-NPC inverters with innovative power semiconductor devices and advanced SOPC control technologies.…”
Section: Implementation and Experimental Resultsmentioning
confidence: 99%
“…Practical implementation issues of the AT-NPC inverters using advanced WBG power semiconductor devices have got attentions in recent years [22] [23]. There still left many design and implementation issues for the integrated design and control of the AT-NPC inverters with innovative power semiconductor devices and advanced SOPC control technologies.…”
Section: Implementation and Experimental Resultsmentioning
confidence: 99%
“…Similarly, the iS1 is constant and vGS_S1 is linearly changed within ton2. The turn-on loss of S1 Pon_S1 can be deduced form Equation (6).…”
Section: Low Side Mosfet Lossmentioning
confidence: 99%
“…Without considering thermal benefits of reduced converter losses, if the feed-in tariff is assumed to be the same as the utility tariff, it can be concluded that the GaN HEMT-based inverter at 10 kHz will bring additional e 30.73 to the owner in comparison with the Si IGBT-based inverter. At 300 kHz, the GaN HEMT-based inverter will not bring significant operation income to the owner, whereas will provide reduction in initial system cost saving due to the reduction in cooling and output filtering requirements [20].…”
Section: A Overall Power Loss and Energy Generationmentioning
confidence: 99%
“…Furthermore, the same devices have been used in other applications, such as resonant L LC dc/dc converters, three-phase inverters, and synchronous buck converters. Those cases have shown the high switching and conduction performance of the GaN HEMT devices in different operating conditions [16]- [20]. Specifically, in [17], GaN devices are demonstrated on a three-phase inverter with 99.3% efficiency at 900-W output power and 16-kHz switching frequency.…”
mentioning
confidence: 95%
See 1 more Smart Citation